2009
DOI: 10.1128/mcb.01275-08
|View full text |Cite
|
Sign up to set email alerts
|

CUX1 and E2F1 Regulate Coordinated Expression of the Mitotic Complex Genes Ect2, MgcRacGAP, and MKLP1 in S Phase

Abstract: Rho GTPases are critical for mitosis progression and completion of cytokinesis. During mitosis, the GDP/GTP cycle of Rho GTPases is regulated by the exchange factor Ect2 and the GTPase activating protein MgcRacGAP which associates with the kinesin MKLP1 in the centralspindlin complex. We report here that expression of Ect2, MgcRacGAP, and MKLP1 is tightly regulated during cell cycle progression. These three genes share similar cell cycle-related signatures within their promoter regions: (i) cell cycle gene hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 62 publications
5
58
1
Order By: Relevance
“…CUX1 is a transcription factor that regulates multiple processes including cell cycle progression, chromosomal segregation and cell migration 29,30 . Consistent with the effects of miR122 silencing described above, CUX1 was reported to modulate cell motility and invasion through the control of RhoA activity [31][32][33] . We observed that whereas CUX1 mRNA levels remained unchanged ( Fig.…”
Section: Establishment Of Mir122-silenced Hcc Cell Linessupporting
confidence: 74%
See 1 more Smart Citation
“…CUX1 is a transcription factor that regulates multiple processes including cell cycle progression, chromosomal segregation and cell migration 29,30 . Consistent with the effects of miR122 silencing described above, CUX1 was reported to modulate cell motility and invasion through the control of RhoA activity [31][32][33] . We observed that whereas CUX1 mRNA levels remained unchanged ( Fig.…”
Section: Establishment Of Mir122-silenced Hcc Cell Linessupporting
confidence: 74%
“…This miR122/CUX1/miR214/ZBTB20/ AFP pathway may explain the deregulated AFP expression observed in HCC cells. Additionally, the ability of CUX1 to activate RhoA and to regulate the expression of many proteins involved in cell motility may explain the increased migration and invasiveness associated with malignancy of HCC [31][32][33][34][35][36] . It should be noted that, although this analysis revealed a trend toward inverse correlation between expression of miR122 and expression of AFP, this correlation could not be applied to all cases examined.…”
Section: Discussionmentioning
confidence: 99%
“…Many transcriptional targets and cellular functions of CUX1 readily suggest mechanisms by which increased p110 or p75 CUX1 expression might promote tumour development and progression, including acceleration of S phase entry 21,22,41,62,63 , stimulation of cell migration and invasion 13,42,[64][65][66] , resistance to apoptosis 14 , and promotion of bipolar mitosis in the presence of supernumerary centrosomes 19 (reviewed in REF. 67).…”
Section: Mechanisms Of Action In Cancermentioning
confidence: 99%
“…17 More recently, p110 CUX1 was found to cooperate with E2F1 and E2F2 in the transcriptional activation of several genes involved in DNA replication and progression through S phase and mitosis. 11,18 Chromatin immunoprecipitation assays revealed that CUX1 enhanced the recruitment of E2F factors to the promoter of these genes.…”
Section: Cellular Processes That Are Commonly Used For Cell Cycling Amentioning
confidence: 99%